THE COMPREHENSION OF THE CONCEPTS OF NOISE AND SILENCE IN PRIMARY SCHOOL CHILDREN - Trinite, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Acoustically ergonomic classrooms prevent teachers’ voice disorders and improve comprehension of learning instructions by pupils. High activity noise in the classroom, which increases voice loudness, is one of the most common complaints by teachers. The aim of the study was to find out how primary school children comprehend the concepts of noise and silence. Two hundred eighty five children representing Grade 1 to four were included in the study. Children were asked to draw how they imagine the silence and noise. Drawings were categorised in the following groups: sources of noise and silence, effects of noise and silence, noisy and silent places. Drawings imagining school environment were analysed separately. We found that primary school pupils can identify noise sources in the classroom, at home, and in environment. They can detect the impact of noise on the psycho-emotional state of the person. Children reflected a much more extensive range of noise generating activities than activities related to silence. The silence was mostly associated with sleeping and learning while noise with positive (singing, playing) and negative (screaming, fighting) actions.Not only teachers but also pupils should know about classroom acoustic ergonomics. Teachers’ education programs should provide education in ergonomics, and teachers should forward this knowledge to children.